2009
DOI: 10.1080/00048670902873722
|View full text |Cite
|
Sign up to set email alerts
|

Clinician-Assisted Internet-Based Treatment is Effective for Depression: Randomized Controlled Trial

Abstract: These results replicate those from the pilot trial reported by Perini et al. and are consistent with literature indicating that Internet-based programmes for depression and other mental disorders combined with clinical guidance can result in clinically significant improvements. These data provide further support for the development of Internet-based treatment for common mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 227 publications
(173 citation statements)
references
References 45 publications
13
149
2
5
Order By: Relevance
“…The availability of internet-based strategies has grown substantially, with demonstrated efficacy in reducing depressive symptoms and improving psychological quality of life (24)(25)(26)(27). The acutely manic bipolar patient may present in an agitated state that acts as a barrier to therapy, interrupts the physician-patient alliance, and creates a disruptive, even hazardous, environment.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
“…The availability of internet-based strategies has grown substantially, with demonstrated efficacy in reducing depressive symptoms and improving psychological quality of life (24)(25)(26)(27). The acutely manic bipolar patient may present in an agitated state that acts as a barrier to therapy, interrupts the physician-patient alliance, and creates a disruptive, even hazardous, environment.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
“…Prior to developing TD iPT, we developed and evaluated disorder-specifi c iPT interventions to treat social phobia Titov, Andrews, Choi, Schwencke, & Mahoney, 2008;Titov, Andrews, Schwencke, et al, 2010;, PD (Wims et al, 2010), GAD , and depression (Perini et al, 2009;Titov, Andrews, Davies, et al, 2010). These interventions were evaluated in 12 RCTs and 3 open trials with participants who met a principal DSM-IV diagnosis for the relevant disorder.…”
Section: Results Of Our Trials Of Disorder-specifi C Iptmentioning
confidence: 99%
“…A substantial number of trials have reported the effectiveness of disorder-specifi c iPT at treating several common mental disorders. For example, more than 10 randomised controlled trials (RCTs) have reported the clinical benefi ts of iPT for clinical and subclinical depression Perini, Titov, & Andrews, 2009;Ruwaard et al, 2009;Titov, Andrews, Davies, et al, 2010), social phobia (Andersson et al, 2006;Berger, Hohl, & Caspar, 2009;Botella et al, 2010;Carlbring et al, 2007;, and panic disorder Klein et al, 2009;Wims, Titov, Andrews, & Choi, 2010). Encouraging evidence has also been found from a smaller but rapidly growing number of RCTs or open trials evaluating iPT for generalised anxiety disorder Robinson et al, 2010;, obsessive compulsive disorder Andersson et al, 2012;Wootton et al, 2011), and post-traumatic stress disorder (Klein et al, 2010;Spence et al, 2011).…”
Section: Internet-delivered Psychological Interventionsmentioning
confidence: 99%
“…The iCBT Sadness Program consists of 6 online lessons representing best practice CBT, as well as regular homework assignments and access to supplementary resources. The Sadness Program has been validated in a number of clinical efficacy and effectiveness trials (28,(32)(33)(34)(35). Each lesson comprises a cartoon narrative in which a character gains mastery over MDD symptoms by learning and implementing CBT skills.…”
Section: Methodsmentioning
confidence: 99%
“…Given the growing burden of OA and depression, the lack of people accessing depression treatment, and the interference of depression with OA treatment outcomes in this population, we investigated the effects of a validated iCBT program for depression (the Sadness Program [28]) in older adults with OA and comorbid depression. To our knowledge, no randomized trial has assessed the effects of an iCBT program for depression in this target population.…”
Section: Introductionmentioning
confidence: 99%